Transfersal Transformation: From Personal Analysis to Social Analysis According to Calvin and Ricoeur - Simon, John C. (Universitas Sanata Dharma, 2019)
Two figures who live in different ages, Calvin and Ricoeur, have built their thinking by way of an experience of repentance or self-renewal. It is this experience what so-called as personal analysis. Calvin, with his experience of